Safety and efficacy of naldemedine in cancer patients with opioid-induced constipation: a pooled, subgroup analysis of two randomised controlled studies - Iwao Osaka; Hiroto Ishiki; Takaaki Yokota; Yukio Tada; Hiroki Sato; Masaharu Okamoto; Eriko Satomi (ESMO Open, 2019)
Objective This post hoc, pooled, subgroup analysis of two randomised studies evaluated baseline characteristics that may influence the efficacy and safety of naldemedine in patients with opioid-induced constipation (OIC) and cancer.Methods Data for patients who received 0.2 mg naldemedine or placebo were pooled from randomised, placebo-controlled, phase IIb and phase III studies. Proportions of spontaneous bowel movement (SBM) responders and patients with diarrhoea were assessed for each treatment group. For the patient subgroups with or without possible blood–brain barrier (BBB) disruptions, changes in Numerical Rating Scale (NRS) and Clinical Opioid Withdrawal Scale (COWS) scores were assessed.Results A total of 307 patients were included in this analysis (naldemedine: n=155; placebo: n=152). The pooled proportion of SBM responders was 73.5% with naldemedine versus 35.5% with placebo. There was a significant increase in the proportion of SBM responders with naldemedine versus placebo (38.0% (95% CI 27.6% to 48.4%); p<0.0001). Greater proportions of SBM responders and patients who experienced diarrhoea were observed with naldemedine versus placebo in all subgroups. Changes from baseline in NRS and COWS scores were similar with naldemedine or placebo in patients with or without brain metastases.Conclusions Although not powered to detect statistically significant differences in treatment effect among subgroups, this study demonstrated that naldemedine appeared to benefit patients with OIC and cancer, irrespective of baseline characteristics, and did not seem to affect analgesia or withdrawal–even in patients with potential BBB disruptions. Baseline characteristics did not appear to affect the incidence of diarrhoea in patients who received naldemedine.Trial registration numbers JapicCTI-111510 and JapicCTI-132340.